Design and development of disk valve exhaust port for four stroke engine - Mohd Nashriq, Mohd Hanafiah (2008)
This report presents the design and development of the disc valve exhaust port. Objectives of this project are to design and develop of disc valves exhaust port for MODENAS KRISS 110cc four stroke engine new cylinder head. In the original engine, a poppet valve is used in the exhaust port. A disc valve will replace the function of the existing poppet valve of controlling the exhaust port opening and closing. This report describe about the design and the working operational of the disc valve in the new cylinder head. The solid modeling of disc valve was designed using the computer-aided drawing software. The disc valve designed used the original valve timing and duration. As a conclusion, the disc valve duration and valve timing is fully controlled by the disc valve shape and design.